The state of the states: Data-driven analysis of the US Clean Power Plan. (July 2016) - Davis, Chris; Bollinger, L. Andrew; Dijkema, Gerard P.J.
Abstract: On August 3, 2015 the US Environmental Protection Agency finalized the Clean Power Plan (CPP) which aims to reduce CO2 emissions from the electricity generating sector by 32% of their 2005 levels by the year 2030. With the rule now finalized, in order to understand how the impact of this will unfold, we need to understand the factors that may influence how the electricity sector evolves given the targets that must now be met. To both identify and understand these relevant factors, we have completed an analysis of US electricity generation data for the period between 2001 and 2014. The result is a detailed fingerprint of the sector per state based on monthly data at the resolution of individual generators. This analysis demonstrates that several "building blocks" or decarbonization strategies encouraged by the CPP are already being utilized in the period analyzed across US states, resulting in CO2 emissions that have already dropped 12% in the period studied. Furthermore, we show how the states exhibit considerable differences due to the complexity of their existing generation portfolios, geography, climate and demand patterns. We also examine to what extent the targets of the CPP may impact the most polluting part of their generation portfolios, and how this relates to developments with shale gas and state policies. We then conclude with an overview of which factors may either enable or hinder how the goals of the Clean Power Plan will be met.